An exploration of status of chronic diseases and its influencing factors of older people in Chinese home care and long-term care facilities: a cross-sectional study - Xie, Fen; Shu, Qingxia; Li, Jinxiu; Chen, Zheng-ying (Frontiers in Public Health, 2023)
Background: As the population ages, the proportion of chronic diseases becomes more prevalent. This study aimed to investigate the current status of chronic diseases among the older people in home care (HC) and long-term care facilities (LTCFs) in China, and to analyze its influencing factors. Methods: A multi-stage stratified random sampling and census sampling approach was used in this survey of the health of 389 HC older people and 202 LTCFs older people from Western Hunan, respectively. Results: The survey showed that the prevalence of chronic diseases among HC older people was 73.26%. The top five chronic diseases were hypertension, bone and joint disease, gastrointestinal and gallbladder disease, heart disease and diabetes. The prevalence of chronic diseases among LTCFs older people was 77.23%. The top five chronic diseases were hypertension, bone and joint disease, cerebrovascular disease, diabetes and heart disease. The results showed that long time spent alone, having sleep disorders, and self-rated health status significantly increased HC older people with chronic diseases prevalence. That having marital status, non-healthy BMI, having sleep disorder, walk with the use of assistive devices, and self-rated health status significantly increased LTCFs older people with chronic diseases prevalence. Conclusion: There are differences in the prevalence and distribution of chronic diseases among older people in two different aged care models in China. And their risk factors for chronic diseases are various. Therefore, chronic disease healthcare strategies should be tailored to two types aged care models for older people. Further summary found that HC older people spend a lot of time alone and suffer from loneliness, which ultimately causes psychological disorders. Thus, psychological adaptation interventions are needed for HC older people. Besides, older people in LTCFs lack social support from their families (divorced/widowed) and have activity disorders (walking with the use of assistive devices). Thus, social adaptation interventions are needed for LTCF older people. This study provides a theoretical basis for the distribution of health care and the prevention and treatment of chronic diseases of Chinese older people.